Price behaviour in India, 1948-49 to 1965-66 : a comparative study of three macro-approaches - Sreenivas, M. A. (Sreenivas ; distributors, Vora, 1974)
Comparison of the theoretical explanations of the price behaviour in India according to the inflationary gap approach, the quantity theory of money, and the cost push theory.